Pathway to care among psychiatric patients attending a Tertiary care hospital in Kathmandu Valley - Rai, N.; Pokhrel, P.; Sharma, P.P.; Basnet, M.; Dahal, B.; Bista, T.B. (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: Mental illness accounts for 14% of all disability adjusted life years (DALYs) lost worldwide and is one of the major contributors to the global burden of disease. In spite of this much of burden and disability there is a huge gap between the treatment and help seeking behavior. Though, the mental illness is a common problem, due to stigma and lack of knowledge they prefer to visit alternative sources like faith healers, traditional practitioners and quacks. Very few of them seek psychiatrists help. So, this pathway to care study aims to provide some descriptive insight into the pathways to care among the psychiatric patients attending the tertiary care hospital in Kathmandu valley. Material and Method: A cross-sectional study among 66 patients seeking psychiatric outpatient services in Kist medical College, Imadole, Lalitpur, Nepal which is a Teriatry hospital from the period of 1st August – 31st October, 2018. Semi structured proforma developed by department of Psychiatry which covered the socio-demographic profile and WHO (1987) collaborative “pathway study” encounter form as a guiding tool was used to collect the data. Results: Out of 66 enrolled patients, 60.6% were in the age group of 21-40. Almost equal proportion of male (51.5%) and female (48.5%) visited psychiatric services. Majority of the patients were married (81.8%), Chhetri (25.8%) by caste and Hindu (81.8%) by religion. Majority of the patients were from outside valley (51.5), educated upto primary level (31.8%) and housewife by occupation (28.8%). The most common diagnosis was Depression (16.7%) and Alcohol Dependence syndrome (16.7%). Majority (45.5 %) of the patients had visited faith healer before visiting to Psychiatrists. 57.6 % patient visited psychiatrists within 2.5 months duration and majority of them were initiated to visit psychiatrists by family members/ relatives. Conclusion: Faith healers were the most common first contact for psychiatric patients. Despite of that majority of the patients had visited psychiatrists within 2.5 months duration. In most of the cases family members/ relatives were the one to initiate for psychiatric consultation.